Prediction and Modeling of Thin Gate Oxide Breakdown Subject to Arbitrary Transient Stresses - Ellis, D F; Yuanzhong Zhou; Salcedo, J A; Hajjar, J; Liou, J J (IEEE transactions on electron devices, 2010)
A reliable dielectric breakdown model under transient stresses via an extension of the power law is demonstrated. The model, which is based on the percolation model and the assumption of no significant detrapping, is successfully used in ramped voltage stress breakdown analysis. A demonstration of the model's validity consists of applying repetitive time-variant voltage waveforms-pulses, sine waves, ramps, and noise-until breakdown and, consequently, comparing prediction to reality. The breakdown distribution is initially derived from DC measurements, with the model predicting both the center and the shape of the distribution.